2017
DOI: 10.1007/s00540-017-2432-1
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative respiratory complications: current evidence and strategy discussed in 2017 JA symposium

Abstract: Respiratory management during general anesthesia aims to safely secure the airway and maintain adequate ventilation to deliver oxygen to the vital organs, maintaining homeostasis even during surgery. Despite its clinical importance, anesthesiologists often encounter difficulties in properly managing respiration during the perioperative period, leading to severe respiratory complications. In this year's JA symposium, 5 editorial board members of Journal of Anesthesia (JA) who are experts in the field of respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Regli et al found that non-OSAS patients were more likely to have increased sleep hypoxemia with nasal packing after general anesthesia ( 19 ). The clinical implication is that although OSAS is an independent predictor of increased risks of complications after general anesthesia ( 11 , 20 22 ), patients with non-OSAS should also be paid attention after bilateral nasal packing because of the high possibility of great deterioration of sleep hypoxemia after general anesthesia. Patients with high modified Mallampati grades are more likely to have glossopharyngeal collapse during sleep ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regli et al found that non-OSAS patients were more likely to have increased sleep hypoxemia with nasal packing after general anesthesia ( 19 ). The clinical implication is that although OSAS is an independent predictor of increased risks of complications after general anesthesia ( 11 , 20 22 ), patients with non-OSAS should also be paid attention after bilateral nasal packing because of the high possibility of great deterioration of sleep hypoxemia after general anesthesia. Patients with high modified Mallampati grades are more likely to have glossopharyngeal collapse during sleep ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, few or no recommendations were suggested to the patient. This point should be discussed in the future regarding the potential risks of these devices and the need for professionals to inform their patients 14-16 .…”
Section: Discussionmentioning
confidence: 99%
“…When used for smoking cessation, a recent Cochrane review pointed out that e-cigarettes may help to stop smoking without any serious side effects 12 . However, their role and effectiveness in managing smoking cessation is unclear and continues to divide the scientific community 13-16 . In 2016, the Food and Drug Administration (FDA) of the USA regulated a rule to cover all tobacco products, including ENDS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations